ACUAN STANDAR INTERNAL GEOKIMIA DENGAN MATRIKS STREAM SEDIMENTS WILAYAH SOREANG, JAWA BARAT - R Irzon; Kurnia Kurnia (Pusat Survei Geologi, 2013)
Certified reference materials are needed in producing a good validity level of measurement process. The closer analytical result of CRM to its certificated value, the better quality of measurement would be. This studi was aimed to produce internal reference material in three kinds of stream sediment matrixes: the first is considered as natural stream sediment, the second suggest to be affected by industrial and anthropogenic actifity, and the last one was taken near by conventional gold mining location. All about sampling location, geological setting and megascopic description of the samples had been collected and saved properly. The three stream sediments samples were homogenized manually and separated in to some split bottles and were prepared and analyzed chemically to show their homogeneity. An Atomic Absorbance Spectrometry and X-Ray Floresence are used to analyze the samples for tatally nine times. Measurement results show that these in-house reference materials are in good level of homogeneity and many chemical elements can be used as a reference value with coefficient of variance <5%. Several factors influence the type of sediment are also reflected in the value of the elements content of each sample, where each example shows the content of the element in accordance with the factors that affect the flow of sediment respectively. This study could be continued further to produce a national reference material in stream sediments matrix.Key words: : in–house reference material, stream sediments, AAS, XRF